Intentional invisibility: Professional women and the navigation of workplace constraints. - Ballakrishnen, Swethaa; Fielding-Singh, Priya; Magliozzi, Devon (Sociological Perspectives, 2019)
Drawing on an in-depth case study at a large nonprofit organization, we find, in line with previous scholarship, that women professionals continue to face biased expectations at work and at home. We leverage data from interviews and participant observation to identify a new strategy that women use to navigate professional constraints created by the second shift and workplace double binds: "intentional invisibility." Intentional invisibility refers to a set of risk-averse, conflict-avoidant strategies that women professionals in our study employ to feel authentic, manage competing expectations in the office, and balance work and familial responsibilities. We find women across the organization reporting intentionally remaining behind the scenes in attempts to avoid backlash and maintain a professional status quo. While intentional invisibility allows women to successfully navigate gender unequal professional and personal landscapes, it could simultaneously present an additional challenge to career advancement. [ABSTRACT FROM AUTHOR]Copyright of Sociological Perspectives is the property of Sage Publications Inc. and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use. This abstract may be abridged. No warranty is given about the accuracy of the copy. Users should refer to the original published version of the material for the full abstract. (Copyright applies to all Abstracts.)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; conciliation famille-travail; discipline; famille; invisibilité intentionnelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail invisible; états-unis

Recherches sur la transitude au Québec: entre absence et exploitation des savoirs trans - Clark Pignedoli; Maxime Faddoul (Genre, Sexualité et Société, 2019)
En suivant l’approche méthodologique de l’autoethnographie, cet article se penche sur la question de l’exploitation des personnes trans en tant que travailleur·se·s précaires de l’université néolibérale. On met en relief la double dynamique d’effacement et d’exploitation des personnes trans « en tant que trans », en soulignant qu’au sein du biocapitalisme, la transitude produit de la valeur qui peut être extraite afin de donner un nouveau souffle aux processus d’accumulation de la richesse. Les conditions de travail des personnes trans dans le domaine de la recherche sont ainsi surdéterminées par ces nouveaux mécanismes d’extractivisme. En guise de conclusion, on partage certaines stratégies de résistance pour renverser cette double dynamique.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; biolcapitalisme; canada; capitalisme; cours; discipline; exploitation; premier cycle; périodes historiques; québec; régions géographiques; résistance; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; trans; travail; travail gratuit; travail social; université; violences; études de genres

Bargaining with confucian patriarchy: Money, culture, and gender division of labor in Taiwanese immigrant families - Gu, Chien-Juh (Qualitative Sociology, 2019)
Previous studies of immigrant families have reported consistent findings concerning the positive effects of employed wives’ financial contributions and Western gender ideologies on women’s bargaining power in the family. This paper revisits this thesis. Data presented in this article are derived from a larger project based on 45 life-history interviews with Taiwanese immigrant women in a Midwest urban region. Findings suggest that women’s employment does not serve as a key factor that shapes spousal power relations in Taiwanese immigrant families. Rather, gendered work-family boundaries and individuals’ abilities construct main rationales in women’s interpretations of their division of labor at home and their dominance in financial management. None of the women interviewed consider Western culture as an inspiration for egalitarian gender ideology. In contrast, Confucian culture is often used by husbands and mothers-in-law to demand traditional gender practice, which is further reinforced and surveilled by the Taiwanese ethnic community. Therefore, the interconnections of work, family, money, culture, and power and their interactive effects on spousal relations are more complicated than previously suggested. This study also reveals varied forms of patriarchal bargaining in Taiwanese immigrant families. Married women tend to accommodate patriarchy in their housework assignment, but actively bargain in their management of family finances and persistence to seek employment. The findings suggest that heterogeneity within the research sample, household structure, and individuals’ subjectivities must be examined to understand the nuances and complexity of women’s gender strategies and bargaining power in immigration families. Theoretical implications of the study are also discussed.
Keywords: amériques; approches et analyses; asie; discipline; famille; femmes* immigrantes; patriarcat; projet charge mentale; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; taiwan; thématiques; travail; travail domestique; états-unis

Les effets du genre sur la charge mentale : une étude sur le mal-être en milieu professionnel - Lanteigne, Amélie (Université de Montréal, 2019)
Ce projet de mémoire a pris forme dans le but d’étudier comment l’effet du genre module la charge mentale au travail, en s’intéressant à l’impact des rapports de genre sur le sentiment de surcharge mentale et comment ils influent sur l’expression du mal-être individuel. L’analyse d’entretiens réalisés auprès de sept femmes et cinq hommes révèle divers facteurs contribuant à l’impression d’être mentalement surchargé au travail : les contraintes temporelles ; l’imprévisibilité ; la précarité au niveau économique et des conditions de travail ; le caractère exigeant des responsabilités professionnelles ; les contradictions du travail ; l’insuffisance du soutien organisationnel ; le manque de reconnaissance au travail ; le faible soutien social ; ainsi que la difficulté à concilier travail et famille. Ces multiples éléments colorent le discours des participants à la fois selon leur genre individuel et selon le type de métier qu’ils occupent : ceux-ci s’inscrivent dans une division relativement bien définie entre métiers majoritairement féminins et métiers majoritairement masculins. Suite à l’analyse des entretiens, il a été possible de cerner des tendances spécifiques à chaque type de métier, qui s’observent dans la relation entre demande psychologique et latitude décisionnelle. Appliqués au modèle de Karasek (1979), les résultats indiquent une conjoncture surchargeante pour les participants occupant un métier à prédominance féminine, où apparaît un cadre organisationnel oppressant. Enfin, de par les effets pernicieux de la non-valorisation du travail traditionnellement féminin et du travail reproductif associé à la gestion familiale, les résultats de cette présente recherche suggèrent que les femmes sont particulièrement à risque d’être surchargées mentalement et de vivre un profond mal-être.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; charge mentale; discipline; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; travail

Travailler la terre et déconstruire l’hétérosexisme: expérimentations écoféministes - Rimlinger, Constance (Travail, genre et sociétés, 2019)
À partir de l’ethnographie de trois lieux ruraux (deux fermes et un gîte) tenus par des femmes lesbiennes et/ou queer qui s’inscrivent dans une critique écologiste et anticapitaliste de la société tout en questionnant les normes de genre et de sexualité, nous interrogerons la signification de ces choix de vie alternatifs au regard de l’identité des actrices et de la manière dont ils enrichissent la compréhension de la constellation des mouvements écoféministes. Nous observerons qu’avec le déplacement de la ville vers la campagne, et du monde salarié vers l’agriculture de subsistance, elles doivent mettre en place de nouvelles stratégies pour lutter contre l’isolement et s’intégrer localement. Simultanément, ce retour à la terre leur offre de nouvelles possibilités d’émancipation, d’engagement et de soutien aux femmes et aux minorités. Le travail agricole, l’engagement féministe et la politisation du quotidien constituent les différentes facettes d’un même projet : celui de chercher une voie plus juste et plus durable pour notre société.
Keywords: 2000 à aujourd'hui; 2010-2019; agriculture; approches et analyses; care; com5170; cours; discipline; environnement; europe; france; hétérosexisme; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; séparatisme lesbien; thématiques; travail; vie rurale; écoféminisme; écologie queer

‘Cold intimacies’ in parents’ negotiations of work–family practices and parental leave? - Twamley, Katherine (Sociological Review, 2019)
This article aims to assess the contention that a ‘feminist’ ideology is associated with a ‘cooling’ of intimacy in heterosexual relationships, as argued by scholars such as Arlie Hochschild and Eva Illouz. According to this thesis, such an ideology, ‘abducted’ by a commercial spirit, encourages women to disengage from warm intimate bonds with others and to prioritize their own personal fulfilment and parity in care and housework. Drawing on two qualitative empirical studies exploring couples’ intimate lives and their feminist and egalitarian preferences and practices in leave, care and housework, this article examines in detail the basis of this thesis, and its effectiveness in explaining the lived experiences of parent couples’ negotiations of this terrain. The data were collected through focus group discussions with parents not sharing leave and a detailed ethnography with couples sharing leave. The comparison shows that, far from observing a clear dichotomy between ‘cold’ feminists and ‘warm’ traditional couples, both sets of parents present a more complex picture of ‘warm’ and ‘cold’ relations. The analysis enables a critical appreciation of sociological theorizing about gender equality and intimacy, contributing to sociological debates around individualism, feminism and family life. © The Author(s) 2018.
Keywords: 2000 à aujourd'hui; 2010-2019; congé parental; discipline; europe; maternité; paternité; projet charge mentale; périodes historiques; royaume-uni; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail de reproduction

Invisible labor and women’s double binds: Collusive femininity and masculine drinking in Russia - Utrata, Jennifer (Gender and Society, 2019)
The heavy drinking of alcohol remains primarily a hegemonically masculine ritual worldwide. Yet scholarship has undertheorized women’s practices in shaping the boundaries of masculine rituals, including drinking. Drawing on 12 months of ethnographic fieldwork and 151 interviews with single mothers, married mothers, nonresident fathers, and grandmothers from diverse class backgrounds, I demonstrate that Russian women perform extensive invisible management labor in attempting to produce responsible men. Constrained by a starkly unequal gender division of domestic labor, wives and mothers engage in varied “patriarchal bargains” as they shape men’s drinking practices, co-producing hegemonic masculinity. Whereas in the Soviet period women also managed men’s drinking, today new gender strategies have emerged. More women are held accountable to a collusive femininity involving both accommodation and resistance, upholding men’s drinking privileges only if breadwinning occurs. As women perform invisible labor, they end up reproducing the conditions that demand this labor from them in the first place. Some women embrace an alternative femininity by becoming single mothers and refusing to manage men’s drinking, especially when men fail as breadwinners. Theorizing collusive and alternative femininities, as well as women’s invisible labor, advances our knowledge of how multiple femininities shape, and may in time change, hegemonic masculinity. © 2019 by The Author(s).
Keywords: approches et analyses; asie; consommation d'alcool; discipline; hégémonie masculine; patriarcat; projet charge mentale; russie; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible